Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 122076 by peter frank last updated on 14/Nov/20

Answered by MJS_new last updated on 14/Nov/20

let t=tan A  ((1+t−(√(t^2 +1)))/( (√(t^2 +1))+t−1))=((1+(√(t^2 +1))−t)/( (√(t^2 +1))+t+1))  (t+1−(√(t^2 +1)))(t+1+(√(t^2 +1)))=−(t−1−(√(t^2 +1)))(t−1+(√(t^3 +1)))  (t+1)^2 −(t^2 +1)=−(t−1)^2 +(t^2 +1)  2t=2t  true

lett=tanA1+tt2+1t2+1+t1=1+t2+1tt2+1+t+1(t+1t2+1)(t+1+t2+1)=(t1t2+1)(t1+t3+1)(t+1)2(t2+1)=(t1)2+(t2+1)2t=2ttrue

Answered by MJS_new last updated on 14/Nov/20

((1+(s/c)−(1/c))/((1/c)+(s/c)−1))=((1+(1/c)−(s/c))/((1/c)+(s/c)+1))  (((c+s−1)/c)/((1+s−c)/c))=(((c+1−s)/c)/((1+s+c)/c))  ((c+s−1)/(−c+s+1))=((c−s+1)/(c+s+1))  (c+s−1)(c+s+1)=(c−s+1)(−c+s+1)  c^2 +s^2 +2cs−1=−c^2 −s^2 +2cs+1  2cs=2cs  true

1+sc1c1c+sc1=1+1csc1c+sc+1c+s1c1+scc=c+1sc1+s+ccc+s1c+s+1=cs+1c+s+1(c+s1)(c+s+1)=(cs+1)(c+s+1)c2+s2+2cs1=c2s2+2cs+12cs=2cstrue

Answered by ajfour last updated on 14/Nov/20

let  sec A=s,  tan A=t  s^2 −t^2 =1 ⇒ ((s−1)/t)=(t/(s+1))  l.h.s. = ((1+t−s)/(s+t−1))=((1−(((s−1)/t)))/(1+(((s−1)/t))))    =((1−((t/(s+1))))/(1+((t/(s+1)))))=((1+s−t)/(s+t+1))=r.h.s. ★

letsecA=s,tanA=ts2t2=1s1t=ts+1l.h.s.=1+tss+t1=1(s1t)1+(s1t)=1(ts+1)1+(ts+1)=1+sts+t+1=r.h.s.

Commented by peter frank last updated on 14/Nov/20

thank you both

thankyouboth

Terms of Service

Privacy Policy

Contact: info@tinkutara.com